Pengolahan Garam Krosok dan Bittern Menjadi Garam Kesehatan - Pranoto, Aris Kabul; Pasaribu, Roberto; Waluyo, Anasri; Pringgenies, Delianis (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2023)
Salt production in the form of coarse salt has a quality with a NaCl salt content of about 94%, which can still meet the requirements as raw material for table salt. Meanwhile, the minimum quality of salt containing NaCl content is required at least 97% for industrial salt needs. Hence, this research aimed to increase the quality of coarse salt from salt farmers to raise the salt selling value by producing health salt. The research method included making a salt house, making salt water with a baume content of about 25-29 Bé°, crystallization, and filtering / draining the Health Salt. The next step was the salt mineral test using the spectrophotometer method. The test results showed that the NaCl content reached 99.35%, while the SNI: 8027:2016 requires a minimum of 97% as industrial salt. Crystal salts are pollutants-free due to the levels of heavy metals (Cadmium, Cd), Mercury (Hg), and minerals that are harmful to health. Iodine, Magnesium, and Calcium are smaller, and the results of laboratory tests are 0.001 mg/kg when compared with SNI: 8027:2016 of 0.1% maximum. Bittern produces very prominent data, namely Magnesium (Mg) with the highest content of 616.67 mg/kg and Potassium (K) of 84.85 mg/kg. It was concluded that the resulting crystal salt qualified as industrial and health salt.